Adiponectin is required for maintaining normal body temperature in a cold environment - Qiong Wei; Jong Han Lee; Hongying Wang; Odelia Y. N. Bongmba; Chia‐Shan Wu; Geetali Pradhan; Zilin Sun; Lindsey A. Chew; Mandeep Bajaj; Lawrence Chan; Robert S. Chapkin; Miao-Hsueh Chen; et al. (2017)
Thermogenic impairment promotes obesity and insulin resistance. Adiponectin is an important regulator of energy homeostasis. While many beneficial metabolic effects of adiponectin resemble that of activated thermogenesis, the role of adiponectin in thermogenesis is not clear. In this study, we investigated the role of adiponectin in thermogenesis using adiponectin-null mice (Adipoq −/−). Body composition was measured using EchoMRI. Metabolic parameters were determined by indirect calorimetry. Insulin sensitivity was evaluated by glucose- and insulin- tolerance tests. Core body temperature was measured by a TH-8 temperature monitoring system. Gene expression was assessed by real-time PCR and protein levels were analyzed by Western blotting and immunohistochemistry. The mitochondrial density of brown adipose tissue was quantified by calculating the ratio of mtDNA:total nuclear DNA. Under normal housing temperature of 24 °C and ad libitum feeding condition, the body weight, body composition, and metabolic profile of Adipoq −/− mice were unchanged. Under fasting condition, Adipoq −/− mice exhibited reduced energy expenditure. Conversely, under cold exposure, Adipoq −/− mice exhibited reduced body temperature, and the expression of thermogenic regulatory genes was significantly reduced in brown adipose tissue (BAT) and subcutaneous white adipose tissue (WAT). Moreover, we observed that mitochondrial content was reduced in BAT and subcutaneous WAT, and the expression of mitochondrial fusion genes was decreased in BAT of Adipoq −/− mice, suggesting that adiponectin ablation diminishes mitochondrial biogenesis and altered mitochondrial dynamics. Our study further revealed that adiponectin deletion suppresses adrenergic activation, and down-regulates β3-adrenergic receptor, insulin signaling, and the AMPK-SIRT1 pathway in BAT. Our findings demonstrate that adiponectin is an essential regulator of thermogenesis, and adiponectin is required for maintaining body temperature under cold exposure.